Design of the Administrative Building of Kuhsar City under a Sustainable Architecture Concept Approach - Mafakheri, H. R.; Hejazi, A. H.; Dashti, M. (Engineering, Technology & Applied Science Research, 2016)
This study investigates a sustainable approach in the design of the administrative building of the municipality and Islamic council of Kuhsar city, Iran. The initial design is inspired by a flower bud and the various stages of the design are described using actual images, 2-D plans and 3-D models. An extra focus is given to sustainable elements. Overall the design aims to deliver an energy sufficient yet aesthetically pleasing building.